LAMINAR SLUG FLOW - HEAT TRANSFER CHARACTERISTICS WITH CONSTANT HEAT FLUX BOUNDARY - Walsh, P; Walsh, E; Muzychka, Y; ASME (2009)
The problem of elevated heat flux in modern electronics has led to the development of numerous liquid cooling devices which yield superior heat transfer coefficients over their air based counterparts. This study investigates the use of liquid/gas slug flows where a liquid coolant is segregated into discrete slugs, resulting in a segmented flow, and heat transfer rates are enhanced by an internal circulation within slugs. This circulation directs cooler fluid from the center of the slug towards the heated surface and elevates the temperature difference at the wall. An experimental facility is built to examine this problem in circular tube flow with a constant wall heat flux boundary condition. This was attained by Joule heating a thin walled stainless steel tube. Water was used as the coolant and air as the segregating phase. The flow rates of each were controlled using high precision syringe pumps and a slug producing mechanism was introduced for segmenting the flow into slugs of various lengths at any particular flow rate. Tube flows with Reynolds numbers in the range 10 to 1500 were examined ensuring a well ordered segmented flow throughout. Heat transfer performance was calculated by measuring the exterior temperature of the thin tube wall at various locations using an Infrared camera. Nusselt number results are presented for inverse Graetz numbers over four decades, which spans both the thermally developing and developed regions. The results show that Nu in the early thermally developing region are slightly inferior to single phase flows for heat transfer performance but become far superior at higher values of inverse Gr. Additionally, the slug length plays an important role in maximizing Nusselt number in the fully developed region as Nu plateaus at different levels for slugs of differing lengths. Overall, this paper provides a new body of experimental findings relating to segmented flow heat transfer in constant heat flux tubes without boiling.Put abstract text here. Copyright © 2009 by ASME.